Examination of the Importance of Patron Saints and Prayer Books in Relation to Pastoral Care in the Police - Szabó, Csaba (Magyar Rendészet, 2016)
This study undertakes to analyse, in the context of previous research carried out in the subject of the pastoral care service in the police force, the regulatory framework within which the veneration of saints is manifested in the Hungarian Police. The teaching of the Catholic Church is becoming more and more important since police work is influenced by ethical issues such as migration, immigration, the situation of minorities.